Nano-Biomimetic Fibronectin/Lysostaphin-Co-Loaded Silk Fibroin Dressing Accelerates Full-Thickness Wound Healing via ECM-Mimicking Microarchitecture and Dual-Function Modulation - Liu CT; Huang LD; Liu K; Pang KF; Tang H; Li T; Huang YP; Zhang WQ; Wang JJ; Yin GL; Hua KZ (International Journal of Nanomedicine)
Chen-Ting Liu,1 Li-Dan Huang,2 Kai Liu,3 Ke-Fan Pang,1 Hao Tang,3 Ting Li,3 Yang-Pei Huang,4 Wei-Qin Zhang,1 Jun-Juan Wang,3 Guo-Li Yin,3 Kou-Zhen Hua3 1School of Clinical Medicine, Hangzhou Medical College, Hangzhou, Zhejiang, 310053, People’s Republic of China; 2Laboratory Medicine, Yiwu Blood Station, Yiwu, Zhejiang, 322000, People’s Republic of China; 3School of Basic Medical Sciences and Forensic Medicine, Hangzhou Medical College, Hangzhou, Zhejiang, 310053, People’s Republic of China; 4School of Laboratory Medicine, Hangzhou Medical College, Hangzhou, Zhejiang, 310053, People’s Republic of ChinaCorrespondence: Kou-Zhen Hua; Guo-Li Yin, School of Basic Medical Sciences and Forensic Medicine, Hangzhou Medical College, Hangzhou, People’s Republic of China, Email 2006031055@hmc.edu.cn; 22007882@qq.comPurpose: In cases of large-area skin defects, the absence of extracellular matrix can lead to difficulties in fibroblast migration, thereby hindering wound healing. This study aimed to address the challenges in treating skin defects by developing a biomimetic nano-dressing that both has antibacterial properties and promotes healing by mimicking the extracellular matrix.Patients and Methods: The electrospun silk protein nanofibers were ultrasonically fragmented into staple fibers. These were then coated and modified by adding a collagen (Col) solution loaded with recombinant lysostaphin (rLys) and fibronectin (Fn), ultimately constructing a biomimetic nanosponge (Fn-rLys-Col/SF-S).Results: In vitro studies have shown that Fn-rLys-Col/SF-S possesses good water vapor balance and antibacterial properties, is non-toxic to cells, and can promote cell proliferation and migration. In vivo experimental results indicated that Fn-rLys-Col/SF-S healed a week earlier than the control group, with the structure of the newly formed skin resembling normal skin at 21 days. Further immunohistochemistry and qRT-PCR results demonstrated that Fn-rLys-Col/SF-S effectively promotes the healing of skin defect wounds by reducing inflammation, promoting angiogenesis, enhancing collagen deposition, and regulating the degree of fibrosis.Conclusion: In conclusion, the Fn-rLys-Col/SF-S biomimetic sponge dressing can promote the repair of skin defects by mimicking the extracellular matrix, providing a potential therapeutic strategy for clinical wound treatment. Keywords: electrospinning, silk fibroin, fibronectin, recombinant lysostaphin, wound healing